Participatory Urban Projects in the Context of Cultural Pragmatics; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Kolodiy N. A. Nataliya Andreevna; Rodionova E. V. Elena Viktorovna; Kolodiy V. V. Vyacheslav Vladimirovich; Ivchik A. A.; Baggio R. Rodolfo (2017, 2017)
Title screen